PSYCHOSOCIAL ASPECTS OF IMPROVING THE EFFICIENCY OF REHABILITATION OF PERSONS WITH DISABILITIES IN COMMUNITY DURING WARTIME - Kolomiiets, Lesia; Shulga, Halina; Lebed, Iuliia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
In the article, the problem of increasing the effectiveness of rehabilitation of persons with disabilities in the community in wartime conditions is updated and substantiated at the theoretical, legal, and empirical levels. On the basis of a focus group survey, the importance and failure to fully realize the problems of rehabilitation of persons with disabilities in the community in wartime conditions were proven. It was established that according to the opinion of persons with disabilities and their parents, the problems of rehabilitation of persons with disabilities are solved to a greater extent by local authorities and local self-government bodies, social services and health care institutions, etc.; there is a need to create a permanent supportive and developmental environment in the community; there is a problem in the organization of work, employment, opportunities to get to work; a violation of the feeling of security is noted, there is a feeling of powerlessness, irritation, misunderstanding of the nearest prospects; fixed need to be listened to and heard, to regularly communicate with specialists. The foreign and Ukrainian experience of psychosocial aspects of increasing the effectiveness of rehabilitation of persons with disabilities in the community is analysed. The author's social project "Different and Equal" is proposed, aimed at improving the efficiency of providing rehabilitation services to persons with disabilities in the community in wartime conditions. The main feature of this social project is that it is maximally focused on integrating the efforts of community members, persons with disabilities and their family members to promote social adaptation, strengthening the resources of persons with disabilities to overcome the challenges and threats of war.